Analisis Usaha Finansial Pengolahan Cocopeat di UMKM Eco Coco Nusantara - Muhammad Kholil Anugrah; Irfan Cholid; Assrorudin Assrorudin; Ira Arianti; A. Nova Zulfahmi (Journal of Applied Accounting, 2026)
Cocopeat is a by-product of coconut husk processing that has high economic value as a growing medium and export commodity. This study aims to analyse the financial feasibility of cocopeat processing at UMKM Eco Coco Nusantara, Sungai Bakau Village, Ketapang Regency, West Kalimantan. The method used is descriptive quantitative with a case study approach through primary data collection consisting of in-depth interviews with the business owner and direct field observation. Financial analysis was conducted by calculating investment, variable, fixed, and total costs; cost of goods sold (COGS); selling price; revenue; income; break-even point (BEP); and benefit-cost ratio (B/C ratio). The results showed that the total equipment investment cost was IDR 79,480,000 with total monthly operational costs of IDR 161,586,310. The COGS of cocopeat was IDR 26,931/sack with a selling price of IDR 70,000/sack, yielding a profit margin of 62% above COGS. Total revenue from the sale of 6,000 sacks/month reached IDR 420,000,000, with a net income of IDR 258,413,690/month. The break-even point (BEP) was at 1,707 sacks/month, or equivalent to IDR 119,471,420, well below the actual production capacity. A B/C Ratio of 2.60 indicates that every IDR 1.00 invested generates a benefit of IDR 2.60. Therefore, the cocopeat processing business at UMKM Eco Coco Nusantara is declared financially feasible and provides significant profit. Keywords: financial analysis, cost of goods sold, break-even point, B/C ratio